An evaluation of recurrent pregnancy loss - Singh, Abha; Kujur, Avinashi; Rathore, Kalpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was aimed to know the demographic profile and categorizes the causes of RPL. Methods: This observational study was carried out in the department of obstetrics and gynecology, Pt. J.N.M. Medical College Raipur from Nov 2015-Sept 2016. Total 100 women were evaluated with history of RPL. Results: 100 women were recruited in our study. The incidence of primary RPL was more than secondary RPL. 48 % women had first trimester abortions. The identifiable causes accounted for 53% out of which anatomical defects were the commonest .Next were endocrinal factors (20%), and Genetic factors (1%),Immunological factors 7%., Medical causes were 3%. However, 47% were unexplained. Conclusions: Despite innumerable investigations, sometimes or rather most of the times, the etiology remains obscure. It is this group of women who become a challenge to manage. Ultimately, most effective therapy for women with unexplained RPL is antenatal counseling, psychological support and tender loving care.